ENT 530 Social Media Portfolio: Kaftanist / Nurul Fatini Saadon - Saadon, Nurul Fatini (2021)
Kaftanist is a online shop that sell all kind of caftan. The main objective is to achieve for variety of customer and offer different design of caftan with an affordable price and high quality caftan. Our target audience is group of people not limit by age, who are looking a sleepwear with a low cost. Our caftan provides a free size and variety of design for them to choose in order to meet their preferences. According to our customer review, our caftan gives and comfortable feeling when wearing it. Especially when the weather is hot, our kaftans give a cold feeling because of the type of fabric used. Our caftan also liked by many customer not limit by the age due to the cheap and affordable prices.